TINGKAT PENDAPATAN, POLA KONSUMSI, DAN POLA MENABUNG PETANI GARAM DALAM PERSONAL FINANCE - Aprilina Susandini; Miftahul Jannah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
Personal finance is a financial management scope was used to manage finances from respective person. A good quality of life requires a good financial and a good financial can be achieved with proper financial planning. Financial management of personal occurs for salt farmers too who have income in seasonal. This study aims to describe Salt farmers Madura income level, consumption, and savings in personal finance. This research conducted on 6 villages on Madura as Salt Island, namely Pangarengan and Ragung in Sampang City, Dasuk and Lembung in Pamekasan city, Karanganyar and Pinggirpapas in Sumenep city. 130 respondents was used on this study with purposive sampling technique and descriptive quantitative as a research method. The results show the factors such as: dry season duration, production, farmer categories, productivity levels, salt prices, profit-sharing system, and side job have effect on income levels. Furthermore, that Madura salt farmers prioritize primary consumption with simple financial management. Besides, Madura salt farm also have savings with various pattern and type. They have gold (Jewelry) investment as the main choice.